Design and Development of Network Reliability based Secure Multicast Routing Protocol for MANET (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
In Mobile Ad hoc network (MANET), link quality and stability of links as well as nodes play a major role. In ad hoc network, links are often changing which could affect the node mobility and integrity of data packets. In this research work, Network Reliability based Secure Multicast Routing Protocol (NRSMRP) is proposed to achieve network reliability by means of creation of reliable multicast tree. This multicast tree is constructed based on link quality and reliability trust metric. In first phase, node categorization and reliability metric calculation are implemented with the help of link quality. In second phase, reliable multicast tree is formed based on parent node and child node. Parent node must have god capacity and signal strength to communicate with child node. In last phase, authentication based multicast routes are established based on the calculation of direct reputation of mobile nodes. From the results, proposed protocol achieves better performance than existing schemes.